Bahasa Inggris Bahasa Inggris - Prahari, Dika; Ramadhanti, Wita (Jurnal Riset Akuntansi Soedirman, 2024)
This study aims to analyze the effect of profitability and leverage on carbon emissions disclosure with media exposure as a moderating variable. The data type used in this research is quantitative causal based on annual and sustainability reports. The objects in this study are companies listed on the Indonesian Stock Exchange (IDX) in the energy sector in the 2020-2022 period. The data analysis techniques are multiple linear regression and moderated regression analysis (MRA). In this study, profitability is measured using Return on Asset (ROA), Debt to Equity Ratio (DER) to measure leverage, and the dependent variable carbon emission disclosure (CED) is measured using the Carbon Disclosure Project taken from research by (Abdullah et al., 2020). The results showed that profitability has a positive effect while leverage has no effect on carbon emissions disclosure. Media exposure does not strengthen the effect of profitability but leverage is proven to strengthen the effect of leverage on carbon emissions disclosure.